Provenance Differences in Water-Use Efficiency Among Sessile Oak Populations Grown in a Mesic Common Garden - Rabarijaona, Arivoara; Ponton, Stéphane; Bert, Didier; Ducousso, Alexis; Richard, Béatrice; Levillain, Joseph; Brendel, Oliver (Frontiers in Forests and Global Change, 2022)
Context: As a widespread species, sessile oak (Quercus petraea) populations occupy a wide range of ecological conditions, which would have favored different locally adapted populations. Water-use efficiency (WUE), defined at the tree level as the ratio of biomass produced to the quantity of water transpired during the same period, is an interesting candidate trait for drought adaptation. Objectives and methods: To investigate whether WUE was a drought-adaptive trait, we studied a sample of 600 trees originating from 16 different provenances, grown for 21 years in a common garden. Intrinsic WUE (WUEi), estimated from the carbon isotope composition (δ13C) of tree rings, was compared among and within populations for three climatically contrasted years. The adaptive character of WUEi was evaluated by relating population mean WUEi, as well as its plasticity to drought, to the mean pedoclimatic conditions of their provenance sites. The contribution of WUEi to tree and population fitness was finally assessed from the relationship between WUEi and tree growth. Results: Significant differences in WUEi were found among populations but a much larger variability was observed within- than among-population. The population WUEi of the juvenile oak trees growing in the relatively mesic conditions of the common garden showed no relationship with a modeled water deficit index for the provenance sites. However, a higher population WUEi plasticity to severe drought was related to a higher proportion of silt and carbon in the soil of the provenance sites. In response to severe drought, populations with a higher increase in WUEi showed a lower decrease in Growth Index (GI). Populations with lower GI reduction in response to drought were from sites with higher vapor pressure deficit in May-July. For the wet year only, populations with a higher WUEi also had a higher GI. Conclusion: The observed correlations between population means of WUEi or GI plasticity to drought and soil and meteorological conditions at the provenance sites suggested a local adaptation of sessile oak regarding drought response strategy. However, the large variability in WUEi observed within populations also suggested that each has the genetic potential to adapt to the predicted drier and hotter conditions.